ZCO/CNT Composites Coated on Silver Substrates as Symmetric Supercapacitor and their Dielectrics Characterization at Various Frequencies - Markus Diantoro; Lisa Ainun Najihah; Ahmad Taufiq; Abdulloh Fuad; Arif Hidayat; Subakti S (Department of Physics, Sebelas Maret University, 2016)
Supercapacitor is a high power density energy storage device which complements the lack of batteries and conventional capacitors. One material which has a great potential in the manufacture of composite supercapacitor is spinel ZnCo2O4/carbon nano tube and abreviated in the later case as ZCO/CNT. Composition variations in ZCO/CNT composites is expected to the performance of supercapacitor especially the dielectric properties and specific capacitance. Inthis study the composite ZCO/CNT was made from raw materials of ZCO nano crystal which was prepared from previous research on which employing sonochemistry technic, carbon nano tube, and 1-methil 2 pyrolidine. A screen printing method was used in this experiment to deposite the composite on silver substrates. The separator in between of two identical composite structures was prepared from isotactic polypropylene. We used KOH 6 M which was implemented as electrolyte of the composites. Characterization of composite structures has been performed using X-RD, while the morphology characterization using SEM. It was found that the dielectric supercapacitor increase by increasing of mass fraction of ZCO in the composite. Thehighest dielectric constant is reached at 1.89 x 106 and the specific capacitance of 81 F/g for 3:1mass ratio of ZCO : CNT at 100 Hz.